The Influence Of Attitude, Subjective Norm, And Perceived Behavior Control On Intentions In Money Wakaf In Indonesia Is Moderate By Indonesian Ulama Endorse - Vilapike , Uthari; Santi, Fitri; Rahmayanti , Dewi (The Manager Review, 2023)
The purposes of this study are to analyze 1).The influence of attitude on the intention to donate money in Indonesia, 2).Effect of subjective norm on the intention to donate money in Indonesia, 3).The effect of perceived behavior control on the intention to donate money in Indonesia, 4).Influence of Indonesian ulama endorse the intention to donate money in Indonesia, 5).The influence of attitude on the intention to donate money in Indonesia moderated by endorse ulama Indonesia, 6).The influence of subjective norm on the intention to donate money in Indonesia is moderated by endorse ulama Indonesia,7).The effect of perceived behavior control on the intention to donate money in Indonesia was moderated by endorse ulama Indonesia using Theory of Reasoned Action and Theory of Planned Behavior. The study used a quantitative approach, nonprobability sampling manifold purposive sampling. The study population was 500 Indonesian muslim respondents aged at least 17 years. The method of data collection using online questionnaires distributed through Google form links. Data analysis techniques in the form of descriptive analysis, hypothesis testing using Smart-PLSc3.0 in the form of outer model test, inner model test and using moderation techniques. The results showed that: 1). Attitude has an average value of 4.24 which is in the very high category, meaning that the attitude is classified as very good. 2). Subjective norm has an average value of 4.25 which is in the very high category, meaning that the subjective norm is classified as very good. 3). Perceived behavior control has an average value of 4.07, which is in the high category, meaning that perceived behavior control is classified as good. 4). The intention to endow money in Indonesia has an average value of 4.11 which is in the high category, meaning that the intention to endow money in Indonesia is classified as good. 5). The endorsement of Indonesian scholars has an average value of 4.19, which is in the high category, meaning that the endorsements of Indonesian scholars are classified as good. The results of testing the quality of data related to the hypothesis, obtained: 1). The effect of attitude on the intention to donate money shows that the original sample is 0.055 which is positive with a p value less than 0.05, namely 0.000, meaning that there is a significant influence between the attitude variable and the intention to donate. money, and H1 is accepted. 2). The effect of the subjective norm on the intention to donate money shows an original sample of 0.030 which is negative with a p value of more than 0.05, namely 0.23, meaning that there is a negative trending influence between the subjective norm variable and the endorsed variable by Indonesian scholars, and H2 is accepted. 3). The effect of perceived behavior control on cash waqf intentions in Indonesia shows an original sample of 0.380 with a p-value of more than 0.05, namely 0.000, meaning that there is a significant influence between the perceived behavior control variable and the intention to endow money in Indonesia and H3 is accepted. 4). The effect of endorsement by Indonesian ulama on the intention to donate money shows that the original sample is 0.598 which is positive with a p value of more than 0.05, which is 0.000, meaning that there is a significant direct effect between the endorsed variable by Indonesian scholars on the intention to donate money and H4 is accepted. 5). The effect of attitude towards the intention to donate money is moderated by the endorsement of Indonesian clerics showing an original sample of 0.032 which is positive with a p value of less than 0.05, namely 0.008 which means significant, meaning a positive moderating effect, and H5 that the endorsement of Indonesian ulema can strengthen the effect of attitude on the intention to endow money in Indonesia. 6). The effect of subjective norms on the intention to donate money in Indonesia is moderated by the endorsement of Indonesian scholars, showing an original sample of 0.029 which is positive with a p value less than 0.05, namely 0.011 which means significant, meaning a positive moderating effect, and H6 that endorses scholars Indonesia can strengthen the influence of subjective norms on the intention to endow money in Indonesia. 7). The effect of perceived behavior control on the intention to endow money in Indonesia is moderated by the endorsement of Indonesian clerics showing an original sample of -0.001 which is negative with a p value of more than 0.05, namely 0.0908 which means significant, meaning H7 that the endorsement of Indonesian clerics can weaken influence perceived behavior control on the intention to endow money in Indonesia.